Alone on the Colorado - Leich, Harold H. (The University of Utah Press, 2019)
"Leich wrote a rich and expressive account of his travels during the Depression--from riding the rails, floating over 200 miles of the Yellowstone River, and finally his attempt to run the Colorado River from its source to the Gulf of Mexico. His writing is wonderfully engaging and this is a grand adventure story to enjoy. He built a kayak and then a wooden boat to run the river. He is the first person known to have run the Colorado River from its source to his unplanned ending in Cataract Canyon. Although the trip ends there and he had to walk out from Hite, Utah, it was his ability to salvage his journal, camera, and film that allows for this wonderful account of his adventure"--Provided by publisher.